Performance tests and design of a series of magnetic fluid shock absorbers with varying stiffness based on optimal stiffness formula - Li, Yanwen; Li, Decai; Li, Yingsong (Frontiers in Materials, 2022)
With the rapid development of aerospace technology, the vibration problem of the spacecraft flexible structure urgently needs to be solved. Magnetic fluids are a type of multi-functional smart materials, which can be employed in shock absorbers to eliminate these vibrations. Referring to the calculation methods of stiffness coefficients of other passive dampers, the stiffness coefficient formula of magnetic fluid shock absorbers (MFSAs) was derived and refined. Meanwhile, a series of varying stiffness magnetic fluid shock absorbers (VS-MFSAs) were proposed and fabricated based on the second-order buoyancy principle. The range of stiffness coefficients covered by these VS-MFSAs contains the optimal stiffness coefficient estimated by formulas. The repulsive force measurement and vibration attenuation experiments were conducted on these VS-MFSAs. In the case of small amplitude, the relationship between the repulsive force and the offset distance was linear, which means the stiffness was linear. The simulation and experiment curves of the stiffness were in good agreement. The results of vibration attenuation experiments demonstrated that the rod length and the magnetic fluid mass influence the damping efficiency of VS-MFSAs. In addition, these results verified that the VS-MFSA with the optimal stiffness coefficient performed best. Therefore, the stiffness coefficient formula can guide the design of MFSAs.